Determinasi Valuasi Perusahaan di Era Investasi Global: Peran Transparansi Emisi Karbon, Performa Lingkungan, dan Ukuran Perusahaan - Nissa Elmawati; Nurlaila Maysaroh Chairunnisa (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2026)
This study seeks to investigate the effect of carbon emission transparency, environmental performance, and firm size on company valuation, while incorporating foreign ownership as a moderating variable. The sample was determined using a purposive sampling approach, comprising energy and consumer non-cyclical firms that consistently published both annual and sustainability reports over the 2021–2023 period. The empirical findings demonstrate that carbon emission transparency and environmental performance exert a positive influence on company valuation. Conversely, firm size is found to be negatively associated with company valuation. With respect to the moderating mechanism, foreign ownership strengthens the relationship between carbon emission transparency and company valuation, as well as the relationship between environmental performance and company valuation. However, foreign ownership attenuates the effect of firm size on company valuation.